2006
DOI: 10.1021/jf062808u
|View full text |Cite
|
Sign up to set email alerts
|

Black Cohosh (Actaea racemosa, Cimicifuga racemosa) Behaves as a Mixed Competitive Ligand and Partial Agonist at the Human μ Opiate Receptor

Abstract: Black cohosh is a commonly used botanical dietary supplement for the treatment of climacteric complaints. Since the opiate system in the brain is intimately associated with mood, temperature and sex hormonal levels, we investigated the activity of black cohosh extracts at the human μ opiate receptor (hMOR) expressed in Chinese hamster ovary cells. The 100% methanol-, 75% ethanol-and 40% 2-propanol-extracts of black cohosh effectively displaced the specific binding of [ 3 H]DAMGO to hMOR. Further studies of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 55 publications
0
60
0
Order By: Relevance
“…We believe that the oral administration of CR extract prior to stress exposure might act as a 5-HT 1A agonist and attenuate SAM or HPA-axis activity. CR extract reportedly acts as a competitive ligand and a partial agonist for opiate receptors (41,42), similar to 5-HT receptors. Additionally, CR extract and isolated cycloartane glycosides have gamma-aminobutyric acid (GABA) A receptor-modulating effects (12), which could also be relevant to the present results.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the oral administration of CR extract prior to stress exposure might act as a 5-HT 1A agonist and attenuate SAM or HPA-axis activity. CR extract reportedly acts as a competitive ligand and a partial agonist for opiate receptors (41,42), similar to 5-HT receptors. Additionally, CR extract and isolated cycloartane glycosides have gamma-aminobutyric acid (GABA) A receptor-modulating effects (12), which could also be relevant to the present results.…”
Section: Discussionmentioning
confidence: 99%
“…A competitive binding assay using a Chinese hamster ovary (CHO) cell line stably transfected with human μ-opioid receptors reported a half-maximal inhibitory concentration (IC 50 ) of 170 μg/mL (27), whereas another found that the CR extract and isolated cycloartane glycosides had γ-aminobutyric acid A receptor (GABA A ) modulating effects (7), which might be relevant to our present results. Although little is known about the pharmacokinetics and metabolites of the CR extract, evidence was recently reported of the bioavailability of actein, which is triterpene glycoside included in the CR extract, after its oral administration to rats (14).…”
mentioning
confidence: 56%
“…It was previously reported that the CR extract behaves as a competitive ligand and partial agonist for opiate receptors (26,27), similar to 5-HT receptors. A competitive binding assay using a Chinese hamster ovary (CHO) cell line stably transfected with human μ-opioid receptors reported a half-maximal inhibitory concentration (IC 50 ) of 170 μg/mL (27), whereas another found that the CR extract and isolated cycloartane glycosides had γ-aminobutyric acid A receptor (GABA A ) modulating effects (7), which might be relevant to our present results.…”
mentioning
confidence: 95%
“…The initially suggested estrogenic activity of lipophilic components, such as triterpenoids, was disproved by later studies (Gaube et al, 2007;Mercado-Feliciano et al, 2012;Hajirahimkhan et al, 2013). There, however, is evidence that A. racemosa L. preparations interact with distinct neurotransmitter systems in the central nervous system, including m-opioid receptors (Rhyu et al, 2006;Reame et al, 2008), serotonin (5-HT) receptors (subtypes 5-HT 1A , 5-HT 1D , and 5-HT 7 ) (Burdette et al, 2003), and dopamine subtype 2 receptors (Jarry et al, 2003). We have previously shown that A. racemosa L. extracts efficaciously modulate GABA A receptors and identified four structurally related cycloartane glycosides in A. racemosa L. extracts as a novel class of GABA A receptor ligands (Cicek et al, 2010).…”
Section: Discussionmentioning
confidence: 99%